Modification of radar signals digital representation - Рогожкин, Е.В.; Подъячий, Ю.И.; Емельянов, Л.Я. (Radiotekhnika, 2019)
The results of modification of the radar signals digital representation aimed at significant reducing the sampling rate when processing both reflections from point objects (airplanes, spacecraft), and incoherent scatter signals from a distributed target are presented. An algorithm for processing such signals is proposed. The calculations confirm the high sensitivity of the proposed variant up to small values of the Doppler shift for large durations of the radar pulse. The developed discrete representation of radar signals is applicable both for incoherent scatter radars and for traditional radars of the active type.